The choice of droplet size probability distribution function for oil spill modeling is not trivial. (February 2021) - Faillettaz, Robin; Paris, Claire B.; Vaz, Ana C.; Perlin, Natalie; Aman, Zachary M.; Schlüter, Michael; Murawski, Steven A.
Abstract: The droplet size distribution (DSD) formed by gas-saturated oil jets is one of the most important characteristics of the flow to understand and model the fate of uncontrolled deep-sea oil spills. The shape of the DSD, generally modeled as a theoretical lognormal, Rosin-Rammler or non-fundamental distribution function, defines the size and the mass volume range of the droplets. Yet, the fundamental DSD shape has received much less attention than the volume median size (d50) and range of the DSD during ten years of research following the Deepwater Horizon (DWH) blowout. To better understand the importance of the distribution function of the droplet size we compare the oil rising time, surface oil mass, and sedimented and beached masses for different DSDs derived from the DWH literature in idealized and applied conditions, while keeping d50 constant. We highlight substantial differences, showing that the probability distribution function of the DSD for far-field modeling is, regardless of the d50, consequential for oil spill response. Highlights: The importance of the oil droplet size distribution function was not known. The distribution function of the DSD drives the oil mass distribution patterns. First response should consider different d50s and probability distribution functions.